FISSURE SEALANT INTERFACE MICROLEAKAGE USING ONE STEP ADHESIVES - Sandy Christiono (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background:This study evaluated the efficacy of a one step adhesives in reducing microleakage after water storage and thermocycling. Method: eighteen freshly extracted caries-free human premolars were used. The teeth were randomly divided into two groups; Group I: control etch adhesive (GC),Group II: G Bond One step adhesive (GC) The teeth were restored using helioseal Vivadent. Group II Each layer was cured using the Spectrum 800 curing light (Dentsply/Caulk) for 20 seconds at 600mW/cm2. The teeth were stored in artifisial saliva for 7 days in incubator. Samples were thermocycled 250x between 5°C and 55°C with a dwell of 30 seconds, then placed in a 0.5% methylene blue dye solution for 24 hours at 37°C. Samples were sectioned longitudinally and evaluated for microleakage at the occlusal and gingival margins under a microscope at 40x magnification. Dye penetration was scored: 0: no microleakage visible, score 1: microleakage up to half of the fissure, score 2: microleakage more than half of the fissure. Result: Mann-Whitney test was used to demonstrate significantly more dye penetration in Group I and Group II. When comparing the scores for two group, the Mann Whitney test showed no significant difference in dye penetration for etch and One step adhesive (p>0.05). Conclusion: Based on the results of this study, it can be concluded that etch and one step adhesive in the fissure sealant no significant difference to reduce of microleakage in study in vitro.